The Romano-African Domus: studies in space, decoration, and function - Carucci, Margherita (2006)
The introduction (chapter I) will present the topic of the present research in two paragraphs. The one will discuss the problems relating to the study of domestic art in Roman Africa and the approach of scholars to them in order to highlight the new aspect of this research. The second one will describe the methodology that will be used in the study of the relationship between architectural forms and mosaic decoration of African domestic architecture during the high and late Empire (Maps 1-2).